The Discourse of Online Media Coverage on the Holly’s Murder - Nur Zaini (BPSDMP KOMNFO Yogyakarta, Kementerian Komunikasi dan Informatika, 2015)
News on the murder of Holly at Kalibata City Apartment, Jakarta on 30 September 2013 has drawn public attention. This study discussed the representation of women in the news on the murder of Holly in online media. Data were analyzed and discussed in patriarchal perspective using the method of critical discourse analysis by Sara Mills. Results showed that online media have represented women as weak, marginal, bad and wrong. In addition, the results also indicated that the four texts Menunjukkan bahwa representasi perempuan have placed men as subject and women as object. The readers were directed to position themselves as men. Keywords: news, representation, women, patriarchy, critical discourse analysis